Sultan Adam Law in The Progressive Law Perspective in Banjar Communities in The 18th Century AD - Muhammad Fahmi Al Amruzi; Masyitah Umar; Anwar Hafidzi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The Sultan Adam Law provides an important and interesting role in the development of the history of law in the Banjar land. This happened during the reign of Sultan Adam Al-Watsiq Billah from 1825 to 1857 AD. This Law contains matters of religion and worship, issues of Governance Law, Marriage Law, Judicial Procedures, Land Law, and Transitional Regulations. This article discusses the role of the Sultan Adam Law in the resolution of religious problems in the Banjar community in South Kalimantan and in Progressive law. The findings of this study are that the Law of Sultan Adam became the guide of the judges in deciding cases, becoming a unifying instrument of the kingdom, and an antidote to deviant sect that developed in the 18th century AD The Sultan Adam Law also exists as a progressive law, because as a a legal instrument, this law can come out of existing traditions and be able to respond to problems that occur in society at that time, and always try to constantly find new meanings and not be bound by absolute meanings. This Law is also able to act as a law that lives in the midst of society and is able to meet their needs.